Kinship Value System on Agricultural Modernization in Farmer Communities in Soki Village Belo District Bima Regency West Nusa Tenggara - Rostati, Rostati; Priyanto, Agustinus Sugeng; Hardati, Puji (Universitas Negeri Semarang, 2019)
Mutual cooperation and rotating work is a business activity carried out by several people, both farmers and farmers or farmers with the government to achieve the same goal of community harmony and economic prosperity. The purpose of this study is to analyze the values ​​of kinship systems towards agricultural modernization of farmers in Soki Village, Belo District, Bima Regency. The research method used is qualitative. The informants in this study were farmers in Soki Village, Belo District, Bima Regency. The technique of collecting data is by observation, in-depth interviews, and documentation. The validity of the data in this study uses triangulation techniques. The results of the study show that the value of mutual cooperation and rotating work carried out by farmers in Soki village are not only in agricultural activities such as planting, cutting, and harvesting. But the community of farmers in the village of Soki conducts mutual cooperation in celebration events such as circumcision, marriage and even at the opening of a new house. Mutual cooperation activities and rotating work have the same goal, namely to alleviate and facilitate work while preserving and applying the culture of the relics of the men.